On the nonlinear parametric resonance of a torsional vibration system with variable generalized masses - Khang, Nguyen Van; Son, Tran Dinh (Vietnam Journal of Mechanics, 1992)
In this paper the nonlinear parametric resonance of a torsional vibration system with variable generalized masses is investigated. The small parameter method is applied to a weakly nonlinear system in order to find its solutions. The stability of the resonance vibrations is studied by the method of Schmidt.